2017
DOI: 10.1177/1550059417723804
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Binocular, Monocular Grating Acuity and of the Visual Interocular Difference in the First 2 Years of Life

Abstract: The sweep visual evoked potential method (sVEP) is a powerful tool for measurement of visual acuity in infants. Despite the applicability and reliability of the technique in measuring visual functions the understanding of sVEP acuity maturation and how interocular difference of acuity develops in early infancy, as well as the availability of normality ranges, are rare in the literature. We measured binocular and monocular sVEPS acuities in 481 healthy infants aged from birth to 24 months without ophthalmologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
2
0
2
Order By: Relevance
“…The mean absolute IAD and upper limits were similar for the VOD > VOS and VOD < VOS types, and both types progressively increase and approach a steady state at 3 years of age. However, systematic variations in the mean IAD have been reported in several studies, indicating that IAD is highest at birth and gradually decreases with age [33][34][35]. Because each type of IAD (VOD = VOS, VOD > VOS, and VOD < VOS) accounted for approximately one-third of all participants in our study and obvious IADs were observed in previous studies [33][34][35][36], we assume that the development of both IAD interocular acuity difference.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The mean absolute IAD and upper limits were similar for the VOD > VOS and VOD < VOS types, and both types progressively increase and approach a steady state at 3 years of age. However, systematic variations in the mean IAD have been reported in several studies, indicating that IAD is highest at birth and gradually decreases with age [33][34][35]. Because each type of IAD (VOD = VOS, VOD > VOS, and VOD < VOS) accounted for approximately one-third of all participants in our study and obvious IADs were observed in previous studies [33][34][35][36], we assume that the development of both IAD interocular acuity difference.…”
Section: Discussionsupporting
confidence: 51%
“…Patterns of similar acuity, better oculus dexter acuity, or better oculus sinister acuity are all possible because the two eyes may be in slightly different developmental stages during early age when acuity develops rapidly [33]. In addition, a remarkable double rise in IAD for the same age group was revealed over 10 years [34,35], which indicates that the developmental differences between two eyes become larger, and infants with IAD can be considered normal only if the IAD is within the upper limits [34]. The results for southern and northern Chinese infants exhibited a considerable gap in acuity levels and the methodologies of both studies were the same.…”
Section: Discussionmentioning
confidence: 94%
“…O protocolo de avaliação funcional desenvolvido nesse estudo, apresenta importantes diferenciais frente aos protocolos nacionais e internacionais disponíveis na literatura. O princípio adotado na confecção de nossos estímulos e com a distância de apresentação estão baseados em estudos de medidas de acuidade visual, a qual define o limiar de separação espacial mínimo para que um estímulo padronizado seja percebido (Costa et al, 2017;Salomão & Ventura, 1995;Mayer et al, 1995). (Salomão & Ventura, 1995;Costa, 2007).…”
Section: Discussionunclassified
“…A importância da visão é facilmente observada pelo interesse de pesquisadores, em diversos países, dedicados ao estudo de funções visuais. A acuidade visual é a função visual mais medida em bebês e crianças (Costa, França, Barboni, & Ventura, 2017;Salomão & Ventura, 1995;Mayer, Beiser, Warner, Pratt, Raye, & Lang, 1995). No entanto, relações entre a acuidade e as demandas funcionais guiadas pela visão em pacientes com alterações no desenvolvimento apresentam apenas moderadas correlações (Barca, Cappelli, Giulio Staccioli, & Castelli, 2010).…”
Section: A R T I G O O R I G I N a Lunclassified
“…A sensibilidade ao contraste e a acuidade visual são medidas usadas para avaliar a qualidade e capacidade da visão humana. A acuidade visual é a função mais medida em bebês e crianças (Costa et al, 2017;Salomão, Ventura, 1995).…”
Section: Introductionunclassified